Hand hygiene compliance among healthcare workers in a tertiary care academic health care organization - Goel, Varun; Gupta, Savita; Bisht, Dakshina; Sharma, Rashmi (International Journal of Research in Medical Sciences, 2020)
Background: Healthcare Associated Infections (HAIs) are a major cause of high morbidity, disability, mortality and rising costs for health systems. Preventing the HAI risk by planning and implementing effective preventive strategies is important to safeguard patient health. Handwashing is one of the fundamental measures for preventing transmission of hospital-acquired infections. Methods: This cross-sectional observational study was conducted in the surgical ICU from January to February 2018 to evaluate the presence of adhesion to the different aspects of HH. Inclusion criteria included all nurses and allied healthcare workers of surgical ICU while all other HCWs were excluded. Two observers collected all HH data. During this analysis, 3000 HH opportunities were observed. HH compliance was tested for all 5 moments as per WHO guidelines. Data thus collected were entered into a computer-based spreadsheet for analysis using SPSS statistical software (version 20) (IBM Corp., NY, USA). Results: Overall hand hygiene compliance observed as per WHO Guidelines was 79.8%. Nurses had an adherence rate of 77.8%; allied staff adherence was 81.8%. Nurses’ compliance after touching patient surroundings was lowest at 60.7%. 96% staff was aware of the facts like diseases prevented by hand washing, ideal duration of HH, reduction of health care associated infections. Conclusions: Overall, the involved ICUs showed low levels of adherence to best hygiene practices with overall compliance of 79.2%. This suggests the need to implement immediate strategies for infection control in the ICUs. A multidisciplinary intervention could be effective in preventing and control the HAI risk.